Electrodiagnosis in diseases of nerve and muscle : principles and practice - Kimura, Jun (Oxford University Press, 2013)
Here is the Fourth Edition of this text. With each subsequent edition, Dr. Kimura has built upon his extensive experience teaching electromyography (EMG) around the world and has transferred his knowledge to the book. It is intended for clinicians who perform electrodiagnostic procedures as an extension of their clinical examination, and will be of value to neurologists and physiatrists who are interested in neuromuscular disorders and noninvasive electrodiagnostic methods, particularly those practicing electromyography (EMG). The book provides a comprehensive review of most peripheral nerve and muscle diseases, including specific techniques and locations for performing each test. The book has been thoroughly updated to reflect the growth that has been made in the field since 2001.